Studi Analitis Dampak Islamophobia dan Strategi Preventif terhadap Masyarakat Indonesia - Fatoni Achmad; Risna Srinawati; Rahma Aristianingsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2021)
Abstract This study aims to determine: 1). The impact that arises due to the emergence of the concept of Islamophobic thinking on the Islamic religion and Islamic society. Solutions that need to be done to counteract Islamophobic thoughts in Indonesian society and anticipate the emergence of sustainable divisions. The method used in this study is qualitative, while the data collection technique uses the library research method. The results of this study: 1). Islamophobia has economic, social, religious, political and educational impacts. 2). Islamophobia can be avoided if the souls of Muslims themselves have strong religious values, awareness of tolerance in interacting, and have adequate intellect.